Dimetindene-Is the minimum toxic dose for children too strict? - Čečrle, Michal; Pelclová, Daniela; Tomáš, Navrátil; Zacharov, Sergej (Basic & clinical pharmacology & toxicology, 2024)
Dimetindene is a sedating antihistamine indicated for the symptomatic treatment of allergic conditions. Dimetindene is marketed among others under the trade name Fenistil (oral solution). Toxicity data are limited, and there is no consensus on the dose at which children require hospitalization. Objective is to determine the potentially toxic dose in children. Data in children with age up to 15 years were obtained from hospital discharge reports. Of 139 paediatric hospital discharge reports, 23 cases (16.5%) were excluded because of uncertain ingestion. In 116 children (46 boys and 70 girls, mean age 2 years and 9 months ± 1 year and 1 month), the majority of children developed no symptoms (87 children, 75%, mean age 3 years±1 year) and the remaining 29 children (25%, mean age 2 years and 11 months ± 1 year and 3 months) developed only mild and spontaneously resolving symptoms of poisoning after a dose of 0.82 ± 0.32 mg/kg b.w. (range 0.26-1.82 mg/kg). In 98% of all cases, hospitalized children were observed for a maximum 24 h, and their condition did not require specific treatment. In conclusion, the prognosis for accidental dimetindene poisoning in children appears to be good and the minimum toxic dose has been determined to be 0.5 mg/kg b.w.
Keywords: toxic dose; children poisoning; dimethinden; otrava; sedating antihistamines; dimetindene; mužské pohlaví; antagonisté histaminu H1; dítě; Dimethindene; Child; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; Poisoning; Histamine H1 Antagonists; Hospitalization; hospitalizace; Female; lidé; Male